Beyond cancer: The potential application of CD47-based therapy in non-cancer diseases - Wei-Qing Deng; Zi-Han Ye; Zhenghai Tang; Xiao-Lei Zhang; Jin-Jian Lu (Acta Pharmaceutica Sinica B)
CD47 is an immune checkpoint widely regarded as a ‘don't eat me’ signal. CD47-based anti-cancer therapy has received considerable attention, with a significant number of clinical trials conducted. While anti-cancer therapies based on CD47 remain a focal point of interest among researchers, it is noteworthy that an increasing number of studies have found that CD47-based therapy ameliorated the pathological status of non-cancer diseases. This review aims to provide an overview of the recent progress in comprehending the role of CD47-based therapy in non-cancer diseases, including diseases of the circulatory system, nervous system, digestive system, and so on. Furthermore, we sought to delineate the promising mechanisms of CD47-based therapy in treating non-cancer diseases. Our findings suggest that CD47-based agents may exert their effect by regulating phagocytosis, regulating T cells, dendritic cells, and neutrophils, and regulating the secretion of cytokines and chemokines. Additionally, we put forward the orientation of further research to bring to light the potential of CD47 and its binding partners as a target in non-cancer diseases.